Digital health interventions in strengthening primary healthcare systems in Sub-Saharan Africa: Insights from Ethiopia, Ghana, and Zimbabwe - Simbini, Tungamirirai; Adimado, Emma; Adjorlolo, Samuel; Guerrero-Torres, Lorena; Srinivas, Prashanth; Zizhou, Simukai; Zerfu, Taddese (Public Library of Science, 2026)
Digital Health Interventions (DHIs) refer to discrete technological functionalities designed to achieve specific objectives in addressing health system challenges. These interventions are considered tools for strengthening health systems, particularly in low- and middle-income countries. This study consolidates findings from Ethiopia, Ghana, and Zimbabwe, examining how three distinct digital health applications with varying intervention components implemented in primary healthcare settings contribute to health system strengthening. The interventions analyzed include Ethiopia’s District Health Information System 2 (DHIS2), Ghana’s District Health Information Management System (DHIMS) and the Lightwave Health Information Management System (LHIMS), and Zimbabwe’s Impilo Electronic Health Record (E-HR) system. In Ethiopia, DHIS2 enhanced health system accountability and data quality by streamlining district-level data aggregation, reporting, and performance monitoring. This led to more informed decision-making and improved resource distribution. In Ghana, DHIMSs functions as a public health-level DHI, facilitating national data-driven performance monitoring, while LHIMS operates at the patient level, supporting patient tracking and management, improving patient workflows and resource tracking. However, a lack of interoperability between these two systems has led to data duplication challenges. Zimbabwe’s Impilo E-HR, a patient-level DHI, has streamlined clinical workflows, improved information sharing, and enhanced decision-making at the point of care. Despite these successes, challenges persist across the three contexts: infrastructure limitations, high staff turnover, and insufficient user technical capacity. Interoperability issues, particularly in Ghana and Ethiopia, hinder seamless data exchange, while sustainability concerns such as funding gaps and inadequate government support undermine the systems’ full potential. The study findings demonstrate that investments in DHIs in primary healthcare may not result in health systems strengthening without addressing baseline conditions for their implementation and sustainability.